Uncommon Location of Common Parasite - Sherwani, P; Tomer, S; Pahuja, L; Anand, R (Nepalese Journal of Radiology, 2014)
Neurocysticercosis is the most common parasitic infection of the Central Nervous System caused by Taenia solium. Spinal cysticercosis is an uncommon site of cysticercal infestation & intramedullary involvement is even rarer.1 We are reporting a rare case of intramedullary cysticercosis in the cervical region in an 11 year old girl who presented with headache & neck stiffness. CT and MRI of the cervical spine done revealed a cystic lesion with mural nodule (scolex) with cord edema in the cervical region. The child underwent treatment with antihelminthic drugs and showed marked clinico-radiological improvement. DOI: http://dx.doi.org/10.3126/njr.v4i1.11373 Nepalese Journal of Radiology, Vol.4(1) 2014: 63-66